Subcutaneously Anchored Sutureless Device for Securement of Chest Tubes in Neonates with Pleural Effusion: Three Case Reports. (11th March 2020) - Rodriguez Perez, Carmen; Romitti, Maria Grazia; Pezzotti, Elena; D'Andrea, Vito; Pezza, Lucilla; Pittiruti, Mauro
Abstract : We report the clinical cases of three neonates, all of them premature, requiring the placement of a chest tube for drainage of a massive pleural effusion. In all three patients, the chest tube was secured using a new subcutaneously anchored sutureless system. This new securement device was easy to insert and to remove, and highly effective in preventing dislodgment. Also, it was not associated to any undesired effect: no sign of pain and/or discomfort and no skin inflammation. The securement device proved to be comfortable and harmless even in fragile patients as neonates, including the frailest ones, the premature. To our best knowledge, this is the first report describing the use of such a device for this purpose.